Brain-Derived Neurotrophic Factor and Extracellular Vesicle-Derived miRNAs in an Italian Cohort of Individuals With Obesity: A Key to Explain the Link Between Depression and Atherothrombosis - Amadio, Patrizia; Macchi, Chiara; Favero, Chiara; Zarà, Marta; Solazzo, Giulia; Dioni, Laura; Sandrini, Leonardo; Vigna, Luisella; Greco, Maria Francesca; Buoli, Massimiliano; Sirtori, Cesare R.; Pesatori, Angela Cecilia; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Obesity and depression are intertwined diseases often associated with an increased risk of cardiovascular (CV) complications. Brain-Derived Neurotrophic Factor (BDNF), altered in the brain both of subjects with depression and obesity, provides a potential link between depression and thrombosis. Since the relationship among peripheral BDNF, depression and obesity is not well-defined, the aim of the present report has been to address this issue taking advantage of the contribution played by extracellular vesicle (EV)-derived miRNAs. Research process: Associations among circulating BDNF, depression and EV-derived miRNAs related to atherothrombosis have been evaluated in a large Italian cohort of obese individuals (n= 743), characterized by the Beck Depression Inventory (BDI-II) score. Results: BDI-II was negatively associated with BDNF levels without a significant impact of the rs6265 BDNF polymorphism; this association was modified by raised levels of IFN-. BDNF levels were linked to an increase of 80 EV-derived miRNAs and a decrease of 59 miRNAs related to atherosclerosis and thrombosis. Network analysis identified at least 18 genes targeted by these miRNAs, 7 of which involved in depression and CV risk. The observation of a possible link among BDNF, depression and miRNAs related to atherothrombosis and depression in obesity is novel and may lead to a wider use of BDNF as a CV risk biomarker in this specific subject group.